Sustained-release opioid following open abdominal urologic surgery: A randomized, controlled study - Vankka, Natalie; Hollman, Dylan; Ghosh, Sunita; Jacobsen, Niels-Erik; Fairey, Adrian; Ip, Vivian (Canadian Urological Association Journal, 2025)
INTRODUCTION: Despite increased risk of adverse events and overdose associated with sustained-release opioids, evidence is lacking to support the short-term use of a low-dose, sustained-release opioid for acute pain control in a monitored setting. Both immediate-release and sustained-release opioids are used clinically in postoperative analgesia. We hypothesized that short-term use of low-dose, sustained-release hydromorphone combined with immediate-release hydromorphone as required would facilitate earlier ambulation after major urologic surgeries compared to immediate-release opioids alone. METHODS: Following ethics approval and patient consent, patients undergoing elective open abdominal urologic surgeries were randomized into two groups: sustained-release hydromorphone on a regular basis for two days, with immediate-release hydromorphone available on an as-required basis; or immediate-release hydromorphone on an as-required basis only. The primary outcome measure was the time to get up and walk three steps. RESULTS: A total of 66 participants were included in the data analysis. There was no statistically significant difference in the time to first mobilization, opioid consumption, or pain scores at any time point between the two groups. There were trends toward more nausea on postoperative days 1, 2, and 3, as well as more severe loss of sleep the first night after surgery in the immediate-release group, although the differences did not reach statistical significance. CONCLUSIONS: Our study showed that patients receiving short-term, low-dose, sustained-release hydromorphone immediately postoperatively did not mobilize sooner compared to those only receiving immediate-release hydromorphone. There was no difference in the pain score or opioid consumption.